Perilaku PKS Lovers Di Media Sosial (Studi Netnografi Tindak Tutur PKS Lovers) - Dini Safitri (Postgraduate of Jayabaya University, 2016)
The purpose of this study provides an overview of the behavior of PKS Lovers in social media post LHI arrested for alleged corruption in the bribery case of imported meat kuoata with PT Indoguna. The impact of these arrests makes the reputation of the PKS which was originally known as the party of ‘clean’ anti-corruption, become lost. In Social Media, PKS was subjected to insults and invective. But the invective then got a reply from PKS Lovers. PKS Lovers presence enliven bustle world of social media. Various political communication text, produced by PKS Lovers, in reaction to the case of LHI and means legislative election campaign in 2014. The method used a qualitative methodology with the method netnografi of the speech act PKS Lovers in social media. The results showed the speech act PKS Lovers shows sporadic activity, it is not managed properly, and reactive. If there is an attack, they attack, but gave the impression of fanaticism and became the target of haters.